2020
DOI: 10.1002/joc.6651
|View full text |Cite
|
Sign up to set email alerts
|

Influence of El Niño‐Southern Oscillation on baroclinic instability and storm tracks in the Southern Hemisphere

Abstract: Earth's weather and climate are strongly influenced by synoptic scale systems such as extratropical cyclones. From this point of view, investigating the mechanisms associated with cyclogenesis, such as baroclinic instability (BI), which are defined by the thermal gradient and wind shear, are extremely important. However, atmospheric teleconnection patterns such as the El Niño-Southern Oscillation (ENSO) phenomenon may affect BI in the preferred region of extratropical cyclones, known as the storm track (ST) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Using the Eulerian approach, Machado et al, 2020 [15] studied the influence of ENSO on the ST distribution in the Southern Hemisphere, and their results corroborated those Reboita et al, 2015 [14]. Machado et al, 2020 [15] concluded that during El Niño periods there is a change in ST position in relation to that in neutral periods and La Niña periods. Machado et al, 2012 [16] and Machado et al, 2015 [17] evaluated BI and STs in the SH for climate change scenarios.…”
Section: Introductionmentioning
confidence: 65%
“…Using the Eulerian approach, Machado et al, 2020 [15] studied the influence of ENSO on the ST distribution in the Southern Hemisphere, and their results corroborated those Reboita et al, 2015 [14]. Machado et al, 2020 [15] concluded that during El Niño periods there is a change in ST position in relation to that in neutral periods and La Niña periods. Machado et al, 2012 [16] and Machado et al, 2015 [17] evaluated BI and STs in the SH for climate change scenarios.…”
Section: Introductionmentioning
confidence: 65%
“…Such increases in both the warm extreme occurrences at the stations and their regional drivers are possibly linked to a latitudinal shift of the storm tracks in association with the El Niño-Southern Oscillation (ENSO) (Turner, 2004;Turner et al, 2016). Machado et al (2021) found that there has been a latitudinal migration of the storm tracks in summer in association with ENSO. The position of the storm tracks is also strongly influenced by the Southern Annular Mode (SAM; Marshall, 2003Marshall, , 2007.…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…Machado et al . (2021) found that there has been a latitudinal migration of the storm tracks in summer in association with ENSO. The position of the storm tracks is also strongly influenced by the Southern Annular Mode (SAM; Marshall, 2003, 2007).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Several modeling studies have discussed the sensitivity between ETCs and initial temperature/moisture fields (Grise et al., 2019; Krishbaum et al., 2018), which has contributed to some contradiction in models either under‐ or over‐estimating forced changes to mean and extreme precipitation (de Vries et al., 2023). Existing literature clearly highlights the importance and effects of increasing moisture on baroclinic eddies and ETCs, but numerous uncertainties remain in how their evolving energetics will manifest as changes to important climate system components such as the Hadley Circulation and the stratification of the extratropical troposphere (O’Gorman, 2011) or the El Nino Southern Oscillation (Machado et al., 2021). Furthermore, to the authors' knowledge, no multi‐decade analysis quantifying regional changes in moisture specifically to baroclinic eddies and ETCs has been done.…”
Section: Introductionmentioning
confidence: 99%